Graduates’ Reflections on the Impact of International Baccalaureate Diploma Program in Tertiary Education: A Case from Turkey (Proceedings of the International Conference on Future of Education, 2021)
The purpose of this study is to explore International Baccalaureate Diploma Program(IBDP) alumni’s perceptions of IBDP education as well as to investigate IBDP graduates’ reflectionsabout the extent to which the IBDP education has impacted their university study at the highereducation in the Turkish context. The study utilized a survey design analyzed quantitatively(descriptive statistics) and qualitatively (content analysis) to collect data from IBDP alumni (N=170out of 347) who graduated from 2012 to 2019 from a national private school implementinginternational education in eastern Turkey. The results of the research revealed that participantsgained the IB learner profile attributes and learned how to become an internationally-mindedindividual through the IB education. Specifically, research participants indicated that they gainedcommunicative skills in a foreign language, academic abilities such as researching as well as criticaland analytical thinking skills, which were transferred to their post-secondary education. However,participants do not think that they are better prepared for the Turkish university entrance examinationthrough the IBDP education they received in their secondary education. This finding is significant toshow the dilemma between international education outcomes and university entrance examinationpreparation. Students’ well-being is another possible area of investigation in the educational contextswhere students are expected to comply with the requirements of both national and internationaleducation. These implications are significant for practitioners for IBDP implementationimprovements at secondary schools as well as for educators for promoting recognition ofinternational education at post-secondary institutions.Keywords: alumni reflections, international education, International Baccalaureate DiplomaProgram, impact study, learner profile, post-secondary education
Keywords: alumni reflections; impact study; learner profile; post-secondary education; international education; International Baccalaureate Diploma Program